Lobectomy versus segmentectomy for stage IA3 (T1cN0M0) non-small cell lung cancer: a meta-analysis and systematic review - Zhang, Wanfei; Chen, Shaogeng; Lin, Xianzuan; Chen, Hongbo; He, Rongqi (Frontiers in Oncology, 2023)
Background: Segmentectomy has been proven to have better survival and perioperative efficacy than lobectomy for non-small cell lung cancer (NSCLC) up to 2 cm. Whether this result is applicable to stage T1cN0M0 NSCLC (2.1 to 3 cm) remains controversial. Methods: We conducted a comprehensive search across seven databases to identify relevant studies comparing lobectomy and segmentectomy procedures. Our primary focus was on survival indicators (overall survival [OS] and disease-free survival [DFS]), while for secondary outcomes, operative outcomes, hospitalization outcomes, recurrences, and complications were considered. Results: After screening, the final analysis included 10 studies (involving 22113 patients in the lobectomy group and 1627 patients in the segmentectomy group). The lobectomy procedure achieved better OS (hazard ratio [HR]: 1.19 [1.07 1.33]) and DFS (HR: 1.37 [1.10 1.71]), which were proven in all subgroups. The OS rate at 2-5 years and DFS rate at 4-5 years were higher in the lobectomy group. The advantages of OS and DFS in the lobectomy group increased over the survival time. More lymph node dissections, intraoperative blood loss and total complications were found in the lobectomy group. Similar hospital stays, 90-day mortality and conversion thoracotomy were found between the two groups. Conclusions: Lobectomy appeared to be the better choice for patients with stage T1cN0M0 NSCLC with better survival (OS and DFS). However, the complications needed to be taken seriously.